C5aR2 Regulates STING-Mediated Interferon Beta Production in Human Macrophages - O'Neill, Luke (My University, 2023)
The complement system mediates diverse regulatory immunological functions. C5aR2, an enigmatic receptor for anaphylatoxin C5a, has been shown to modulate PRR-dependent pro-inflammatory cytokine secretion in human macrophages. However, the specific downstream targets and underlying molecular mechanisms are less clear. In this study, CRISPR-Cas9 was used to generate macrophage models lacking C5aR2, which were used to probe the role of C5aR2 in the context of PRR stimulation. cGAS and STING-induced IFN-β secretion was significantly increased in C5aR2 KO THP-1 cells and C5aR2-edited primary human monocyte-derived macrophages, and STING and IRF3 expression were increased, albeit not significantly, in C5aR2 KO cell lines implicating C5aR2 as a regulator of the IFN-β response to cGAS-STING pathway activation. Transcriptomic analysis by RNAseq revealed that nucleic acid sensing and antiviral signalling pathways were significantly up-regulated in C5aR2 KO THP-1 cells. Altogether, these data suggest a link between C5aR2 and nucleic acid sensing in human macrophages. With further characterisation, this relationship may yield therapeutic options in interferon-related pathologies.
PUBLISHED
Keywords: complement; anaphylatoxin C5a; regulatory immunological functions; interferon beta; cGAS-STING; innate immune sensing; C5a; anaphylatoxin receptor; C5aR2; pattern recognition receptor